2017
DOI: 10.1542/peds.2016-3659
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Diaphragmatic Hernia and Growth to 12 Years

Abstract: Poor linear growth persisted at 12 years of age. The pattern of early deterioration of weight gain followed by a decline in linear growth is suggestive of inadequate nutrition during infancy. Therefore, nutritional assessment and intervention should be started early and should be continued during childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 31 publications
5
16
0
Order By: Relevance
“…In the combined cohort, there were 210 (59%) male and 147 (41%) female CDH patients. The gender distribution with increase male prevalence (1.4:1) is consistent with published retrospective and prospective studies 15, 16 . Among the 148 complex cases, the most frequent anomalies were congenital heart disease (41%), but neurodevelopmental delay, gastrointestinal, and other malformations were common (Table 1 and Supplementary Table 2).…”
supporting
confidence: 91%
“…In the combined cohort, there were 210 (59%) male and 147 (41%) female CDH patients. The gender distribution with increase male prevalence (1.4:1) is consistent with published retrospective and prospective studies 15, 16 . Among the 148 complex cases, the most frequent anomalies were congenital heart disease (41%), but neurodevelopmental delay, gastrointestinal, and other malformations were common (Table 1 and Supplementary Table 2).…”
supporting
confidence: 91%
“…This trend continued into adolescence, demonstrating stunting in both groups that was most severe in the ECMO population. Notably, none of the patients were feeding tube dependent by 8 years of age . This study highlights the ongoing nutrition challenges of children with CDH and the need for close follow‐up and multidisciplinary interventions.…”
Section: Nutrition‐related Outcomes In Neonatal Ecmo Survivorsmentioning
confidence: 80%
“…22 Approximately 20-30% experience FTT within the first few years of life which may persist into adolescence. 87,88 However, Gien et al 89 revealed the highest risk for comorbidities at both extremes of growth velocity. Leeuwen et al 88 observed stunting and wasting up to 12 years of age, although growth failure became less prevalent after correcting for individual target height.…”
Section: Literature Review Pulmonary Function a Literature Overview mentioning
confidence: 99%
“…87,88 However, Gien et al 89 revealed the highest risk for comorbidities at both extremes of growth velocity. Leeuwen et al 88 observed stunting and wasting up to 12 years of age, although growth failure became less prevalent after correcting for individual target height. Several risk factors expressing the severity of CDH have been identified: the intensity of respiratory support, ECMO use, and oxygen supplementation at discharge.…”
Section: Literature Review Pulmonary Function a Literature Overview mentioning
confidence: 99%